Cone morse x external hexagon, advantages and disadvantages in the clinical aspect: literature review (Research, Society and Development, 2020)
Objective: Dental implants are increasingly present in the daily routine of dentistry, with the Morse taper and external hexagon type being the most frequently used. The present work aims to compare, according to a literary review, the clinical aspects between the morse cone and external hexagon systems of dental implants. Methodology: A selection of scientific articles was made from the Bireme, Pubmed and Scielo databases using the descriptors "cone morse", "external hexagon" and "dental implants". Works published between 2006 and 2018 were included. Of the 622 articles found and delimited by the inclusive criteria, 27 articles were selected as a sample, which presented the theme listed for the research and which were discussed in the following topics: a) peri-implantitis; b) mechanics; c) aesthetics. Results: The morse cone system has advantages in terms of interface sealing, which results in less micro-infiltrations by micro-organisms that cause peri-implantation and has superior mechanics when compared to the external hexagon. Conclusion: Although it presents advantages in relation to micro-infiltration and mechanics, the Morse taper system still costs more than the external hexagon and it is up to the patient to take effective care with oral hygiene and consequent maintenance of the implant, regardless of the system used.